Suhu Penyangraian Terhadap Sifat Fisikokimia Biji KopiRobustaKayu Aro KerinciProvinsiJambi Roasting Temperature on Physicochemical Properties of Kayu AroKerinci Robusta Coffee Beans Jambi Province - Yosua Sihotang; Noviar Harun; Raswen Efendi (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2021)
Roasting is the process of forming the distinctive aroma and taste of coffee from coffee beans carried out using high temperatures. Currently there is little literature on how to properly roast coffee products to produce quality roasted coffee. This research was conducted to determine the effect of roasting temperature on changes in the physicochemical properties of robusta coffee. The research design used was a completely randomized design (CRD) with roasting temperature treatments consisting of 190 °C, 200 °C, 210 °C, 220 °C, 230 °C, and 240 °C. Baking is 10 minutes. The results showed that the roasting temperature treatment affected the moisture content, ash content, acidity, caffeine content, aroma (hedonic), and color of robusta coffee. The temperature chosen for roasting 190 °C with a roasting time of 10 minutes is the best treatment to produce the best physicochemical properties, namely with water content of 2.35%, ash content of 4.01%, degree of acidity (pH) 5.16, caffeine content of 1 , 13%, aroma score 3.90, color index L 26.64.Keywords: robusta coffee, roasting, roasting temperature